Annulations with Butenolides and Phthalides: New Entries to Isocoumarins, 3,4-Dihydroisocoumarins, and Benzofurans - Wang, Shuai; Kraus, George A. (Synthesis, 2020)
The reactions of the anions of butenolides and substituted phthalides with sorbate esters and mono-epoxy sorbate esters furnish isocoumarins, 3,4-dihydroisocoumarins, and benzofurans. The yields range from 41% to 71%.
Keywords: butenolides; phthalides; sorbate esters; epoxy sorbates; polycyclic ring; isocoumarins; benzofurans; cyclic annulation